Employee Branding And Service Quality: The Moderating Effect Of Employees’ Role Behavior (Sains Humanika, 2015)
The purpose of this study is to identify relationship between employee branding and service quality as well as the moderating effect of employees’ role behavior on the employee branding-service quality relationship. It presents the findings from a questionnaire survey of 370 shoppers in one of the shopping complex located at Southern region of Malaysia. The results of hierarchical multiple regression analysis revealed that there is a significant moderating effect of employees’ role behavior on the employee branding-service quality relationship. The findings may be useful in designing customer retention strategies that are related to the retailing business. Implications, limitations of study and suggestions for future study are also explored.
Keywords: Employee branding; service quality; employees' role behavior; Malaysia